General Situation of the Science of History and Archeology in Turkestan in the Second Half of the 19th Century and the Early 20th Century (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, the author describes the development of the science of history and archeology in Turkestan on the basis of modern research. An analysis of sources about local history scientists, researchers and local collectors in Turkestan is presented.